Volume 3: 21st International Conference on Advanced Vehicle Technologies; 16th International Conference on Design Education 2019
DOI: 10.1115/detc2019-97763
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rider Posture on Bicycle Comfort

Abstract: Cyclists are exposed to vibration due to road roughness. The levels of vibration that the cyclists experience have a major effect on comfort and depend on the bicycle, rider and road characteristics. It is known that the posture of the cyclist has a relevant effect on the bicycle-cyclist system vibration response. Nevertheless, this effect has been scarcely quantified. This study focuses on the measurement of the effect of body posture on comfort while riding a bicycle. A laboratory methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These differences may be caused by some phenomena that are present on the road but are not considered in laboratory tests. On the road, due to the active state of the rider, the body posture may differ from the one adopted during the laboratory tests [8,36]. Even if the quality of the bicycle lane is good, the presence of small localised defects that generate impulsive excitations is unavoidable.…”
Section: Comparison Between Laboratory Predictions and Road Tests Resultsmentioning
confidence: 99%
“…These differences may be caused by some phenomena that are present on the road but are not considered in laboratory tests. On the road, due to the active state of the rider, the body posture may differ from the one adopted during the laboratory tests [8,36]. Even if the quality of the bicycle lane is good, the presence of small localised defects that generate impulsive excitations is unavoidable.…”
Section: Comparison Between Laboratory Predictions and Road Tests Resultsmentioning
confidence: 99%
“…In fact, for e-scooters the driver represents almost 90% of the total mass of the system and its dynamic properties significantly influence the overall dynamic behavior of the vehicle. This has been proven for bicycles, that show a driver/vehicle mass ratio like that of e-scooters, for which it has been demonstrated that the rider posture influences its comfort [5] and that the modal properties of the system with or without the rider change significantly [6].…”
Section: Introductionmentioning
confidence: 91%